Strategic Planning on the Local Level As a Factor of Rural Development in the Republic of Serbia - Zoran Njegovan (European Regional Science Association (ERSA), 2006)
The policy of regional rural development has to be efficient. It must relay on so called "good governance". But in last few decades the results on this segment in the republic of Serbia couldn't be qualified as significant. So the primary objective of the paper is focused on how to reverse the process of continued impoverishment of the local rural areas and create conditions for social, cultural, economic and environmentally sustainable development based on local initiative. In order to meet this objective, an attempt is made to define systematic, continuous and cyclic approach of setting up priorities and policies as a basic tool for strategic action planning on a local level (LSAP). Decentralization of the state, strengthening of local municipalities and participation of citizens are three processes which had to be articulated and which through their validity has to gain strength and importance in republic of Serbia. The paper can provisionally be divided into two parts. The first part encompasses the importance of local strategic planning as well as justification of theoretical approaches while the second part gives the bases for methodology of strategic action planning on the local level formulation. In such approach two basic preconditions of LSAP could be specified: adequate institutional base i.e. strong participation of local community and its main stakeholders like local government, citizens, NGO's and others; as well as high level of professional knowledge which builds local stakeholders ability of planning. Introducing of the regional rural approach on the local level is connected with development of LSAP in three basic sectors: institutional – civil society, infrastructural and economic. Local community must be aware what does LSAP mean, why it is so important, what preconditions are important in its development, how it's structure look like, how it has to be developed, and how to stimulate local initiative, participation, transparency and democracy to reach sustainability.
Keywords: 330